Protonation/reduction dynamics at the [4Fe–4S] cluster of the hydrogen-forming cofactor in [FeFe]-hydrogenases. Issue 5 (8th September 2017) - Senger, Moritz; Mebs, Stefan; Duan, Jifu; Shulenina, Olga; Laun, Konstantin; Kertess, Leonie; Wittkamp, Florian; Apfel, Ulf-Peter; Happe, Thomas; Winkler, Martin; Haumann, Michael; Stripp, Sven T.
Abstract : FTIR spectroscopy and DFT calculations were used to identify a protonation at the catalytic cofactor of [FeFe]-hydrogenases. Abstract : The [FeFe]-hydrogenases of bacteria and algae are the most efficient hydrogen conversion catalysts in nature. Their active-site cofactor (H-cluster) comprises a [4Fe–4S] cluster linked to a unique diiron site that binds three carbon monoxide (CO) and two cyanide (CN − ) ligands. Understanding microbial hydrogen conversion requires elucidation of the interplay of proton and electron transfer events at the H-cluster. We performed real-time spectroscopy on [FeFe]-hydrogenase protein films under controlled variation of atmospheric gas composition, sample pH, and reductant concentration. Attenuated total reflection Fourier-transform infrared spectroscopy was used to monitor shifts of the CO/CN − vibrational bands in response to redox and protonation changes. Three different [FeFe]-hydrogenases and several protein and cofactor variants were compared, including element and isotopic exchange studies. A protonated equivalent (HoxH ) of the oxidized state (Hox ) was found, which preferentially accumulated at acidic pH and under reducing conditions. We show that the one-electron reduced stateHred′ represents an intrinsically protonated species. Interestingly, the formation ofHoxH andHred′ was independent of the established proton pathway to the diiron site. Quantum chemical calculations of the respective CO/CN − infrared band patterns favored a cysteine ligand of the [4Fe–4S] cluster as the protonation site inHoxH andHred′ . We propose that proton-coupled electron transfer facilitates reduction of the [4Fe–4S] cluster and prevents premature formation of a hydride at the catalytic diiron site. Our findings imply that protonation events both at the [4Fe–4S] cluster and at the diiron site of the H-cluster are important in the hydrogen conversion reaction of [FeFe]-hydrogenases.